2020
DOI: 10.1103/physrevx.10.011023
|View full text |Cite
|
Sign up to set email alerts
|

Synchronization to Big Data: Nudging the Navier-Stokes Equations for Data Assimilation of Turbulent Flows

Abstract: Nudging is an important data assimilation technique where partial field measurements are used to control the evolution of a dynamical system and/or to reconstruct the entire phase-space configuration of the supplied flow. Here, we apply it to the canonical problem of fluid dynamics: three-dimensional homogeneous and isotropic turbulence. By doing numerical experiments we perform a systematic assessment of how well the technique reconstructs large-and small-scale features of the flow with respect to the quantit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 69 publications
4
38
0
Order By: Relevance
“…dissipation lengths can be slaved by the larger-scale motions. Similar estimates were obtained by Yoshida, Yamaguchi & Kaneda (2005) and Clark Di Leoni, Mazzino & Biferale (2020) in their investigations of data assimilation of small scales from knowledge of the large scales in IHT. Henshaw et al (2003) also conjectured that the disparity found in the size of the synchronizable subspaces should be attributed to the enhanced dissipation that occurs in the strong deformation regions forming in the flow, which is not captured in the analysis of Foias & Prodi (1967) and Ladyzhenskaya (1975).…”
Section: Introductionsupporting
confidence: 83%
“…dissipation lengths can be slaved by the larger-scale motions. Similar estimates were obtained by Yoshida, Yamaguchi & Kaneda (2005) and Clark Di Leoni, Mazzino & Biferale (2020) in their investigations of data assimilation of small scales from knowledge of the large scales in IHT. Henshaw et al (2003) also conjectured that the disparity found in the size of the synchronizable subspaces should be attributed to the enhanced dissipation that occurs in the strong deformation regions forming in the flow, which is not captured in the analysis of Foias & Prodi (1967) and Ladyzhenskaya (1975).…”
Section: Introductionsupporting
confidence: 83%
“…The synchronisation of chaotic systems is a well-known and widely studied phenomenon with important consequences and applications in the natural sciences and engineering (Pecora & Carroll 1990). See Di Leoni, Mazzino & Biferale (2020) for a recent application to turbulence. In general, two or more chaotic systems are said to be synchronised when all, or some, of their state variables evolve towards a common spatio-temporal pattern under the action of a driving force or coupling.…”
Section: Synchronisation Experiments In Isotropic Turbulencementioning
confidence: 99%
“…if more information about the flow state is available from PIV data. Recent state estimation tests in homogeneous isotropic turbulence (Yoshida, Yamaguchi & Kaneda 2005;Lalescu, Meneveau & Eyink 2013;Di Leoni, Mazzino & Biferale 2019;Li et al 2020) demonstrated that the reconstruction of turbulence is successful only when the highest wavenumber k m of velocity data satisfies k m η > 0.2, where η is the Kolmogorov scale of the flow. In wall turbulence, however, flow inhomogeneity in the wall-normal direction, the wall-normal dependence of mean advection and the turbulence production all preclude adopting the same criterion from the homogeneous case.…”
Section: Introductionmentioning
confidence: 99%